Can Sustainable Investing Save the World? Reviewing the Mechanisms of Investor Impact. (December 2020) - Kölbel, Julian F.; Heeb, Florian; Paetzold, Falko; Busch, Timo
This article asks how sustainable investing contributes to societal goals, conducting a literature review on investor impact—that is, the change investors trigger in companies' environmental and social impact. We distinguish three impact mechanisms: shareholder engagement, capital allocation, and indirect impacts, concluding that the impact of shareholder engagement is well supported in the literature, the impact of capital allocation only partially, and indirect impacts lack empirical support. Our results suggest that investors who seek impact should pursue shareholder engagement throughout their portfolio, allocate capital to sustainable companies whose growth is limited by external financing conditions, and screen out companies based on the absence of specific environmental, social, and governance practices that can be adopted at reasonable costs. For rating agencies, we outline steps to develop investor impact metrics. For policy makers, we highlight that sustainable investing helps diffuse good business practices, but is unlikely to drive a deeper transformation without additional policy measures.